Critical times, memoirs of a South Asian diplomat - Ahmed, Fakhruddin, 1931- (Dhaka : University Press, 1994)
Personal accounts of Fakhruddin Ahmed, b. 1931, of his experiences during his career in the foreign service of Bangladesh and his postings to the various capitals of the world.
Includes bibliographical references and index.
Keywords: Ahmed, Fakhruddin, -- 1931-; Bangladesh -- Foreign relations; Bangladesh -- Politics and government -- 1971-; Diplomats -- Bangladesh -- Biography